Enhancing The Readiness of Vocational High School Students in Facing the Era of Digitalization and Artificial Intelligence - Nizmi, Yusnarida Eka; Hidayati, Umunnisa; Alby, Syahroni; Olivia, Yessi; Wicaksa, Arif; Yuniarti, Anik; Issundari, Sri; Ratnawati, Ratnawati; Ibrahim Roni Surya Hasibuan, Ahmad (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2026)
Digitalization and the development of artificial intelligence (AI) have driven significant transformations in the global workforce structure. Vocational High School (VHS) graduates face serious challenges in an increasingly dynamic industrial landscape, such as a high risk of unemployment due to a mismatch between their skills and industry needs. This article discusses the implementation of community service activities aimed at improving vocational high school students’ readiness to enter the digital-based world of work through a participatory educational approach. These educational activities were conducted at a private vocational school in Sleman, Yogyakarta. The method used included participatory educational outreach, whose activities were analyzed descriptively. The results indicate an increase in students’ understanding and readiness to integrate technical and non-technical skills, as well as an increased awareness of the importance of reskilling and upskilling. The majority of students are immediately oriented towards work after graduation and demonstrate a positive perception of their technical competencies, although they still need to strengthen their interpersonal and adaptive skills.Digitalisasi dan perkembangan kecerdasan buatan (Artificial Intelligence/AI) telah mendorong transformasi yang signifikan dalam struktur tenaga kerja global. Lulusan Sekolah Menengah Kejuruan (SMK) menghadapi tantangan serius di tengah lanskap industri yang semakin dinamis, seperti tingginya risiko pengangguran akibat ketidaksesuaian antara kompetensi yang dimiliki dengan kebutuhan industri. Artikel ini membahas pelaksanaan kegiatan pengabdian kepada masyarakat yang bertujuan meningkatkan kesiapan siswa SMK untuk memasuki dunia kerja berbasis digital melalui pendekatan edukasi partisipatif. Kegiatan edukasi tersebut dilaksanakan di salah satu SMK swasta di Sleman, Yogyakarta. Metode yang digunakan berupa penyuluhan edukatif partisipatif, dengan analisis kegiatan dilakukan secara deskriptif. Hasil kegiatan menunjukkan adanya peningkatan pemahaman dan kesiapan siswa dalam mengintegrasikan keterampilan teknis maupun nonteknis, serta meningkatnya kesadaran akan pentingnya reskilling dan upskilling. Sebagian besar siswa berorientasi untuk langsung memasuki dunia kerja setelah lulus dan menunjukkan persepsi positif terhadap kompetensi teknis yang dimiliki, meskipun mereka masih perlu memperkuat keterampilan interpersonal dan kemampuan beradaptasi.